Erysiphe pakistanica (Erysiphaceae), a new species on Indian willows (Salix tetrasperma) from Pakistan - Afshan, Najam-Ul-Sehar; Riaz, Maria; Liaqat, Nida; Majeed, Javeria; Jabeen, Muhammada; Niazi, Abdul Rehman; Khalid, Abdul Nasir; Zafar, Irsa; Afzal, Saliha (Phytotaxa, 2022)
A new powdery mildew fungus, Erysiphe pakistanica (Erysiphaceae) infecting Indian willows is described from north-western areas of Pakistan. Identification is based upon morpho-anatomical features and molecular analysis. This species is characterized by having nipple-shaped appressoria, small chasmothecia and ascospores. Phylogenetic analysis of nrDNA of ITS and LSU regions of E. pakistanica supports its novel identity within the genus Erysiphe (Sect. Uncinula). A comprehensive description along with photographs and phylograms to show its exact position and a comparison with closely related taxa is provided.